Kebersihan Gigi dan Mulut Anak Usia 11-12 Tahun Berdasarkan Teknik Menyikat Gigi Kombinasi - Herawati, Nova; Ramadhani, Raja Prisila; Yuzar, Yessi; Lisnayetti, Lisnayetti; Alhamda, Syukra (Poltekkes Kemenkes Padang, 2025)
Dental and oral health problems are still a serious concern in Indonesia. Based on SKI data in 2023, 56.9% of the population experienced dental and oral health problems, where dental caries is the most common problem caused by plaque. Vertical, horizontal, roll, and Fone's techniques are recommended techniques for children because they are simple and commonly used in everyday life. The purpose of this study was to prove the differences in dental and oral hygiene of children aged 11-12 years who brush their teeth with a combination of vertical, roll, horizontal and vertical, Fone’s, horizontal combination techniques at SDN 11 Bungo Tanjuang, Tanah Datar Regency. This study used a quasi experiment method with a pretest and posttest design. The population amounted to 42 people. Saturated sampling technique is used in sampling. Dental and oral hygiene is measured using the Hygiene Index. Data analysis was carried out using the Independent T-test statistical test. The results showed an average difference in oral hygiene for the vertical, roll, horizontal combination technique of 34% and for the vertical, Fone’s, horizonta combination technique of 18.95%, with a p-value of 0.000 (≤ 0.05). In conclusion, the combination of vertical, roll, and horizontal techniques is more effective in improving dental and oral hygiene scores. Students are advised to brush their teeth using the combination of vertical, roll, and horizontal techniques taught to them routinely twice daily to maintain dental and oral hygiene.